1980
DOI: 10.1159/000232545
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Immune Response to <i>Mycobacterium lepraemurium</i>

Abstract: Evaluation of the cell-mediated immune response (CMI) in mice infected with Mycobacterium lepraemurium revealed a disturbance in the nonspecific components of the CMI. Expression of delayed type hypersensitivity (DTH) in skin test studies indicated that the organism is capable of inducing skin reactivity in mice. This begins at a very early stage of infection and subsequently decays as the infection becomes disseminated. At this stage, gross pathological changes are noticed followed by a high rate of mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We have shown that proliferative responses to ConA and to allogeneic cells were depressed throughout MLM infection, whereas no significant modification in the generation of CTL could be detected. It has been well established that the inoculation of rats and mice with large doses of MLM or other pathogenic mycobacteria induces deficits of in vitro immune functions, such as responses to polyclonal T-cell mitogens (32,38) and specific antigens (21) and an impairment of in vivo T cell-mediated immunity, such as delayed skin graft rejection (6,23), reduced delayed-type hypersensitivity response to sheep erythrocytes (6), and T-dependent antibody response to sheep erythrocytes (5,25,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that proliferative responses to ConA and to allogeneic cells were depressed throughout MLM infection, whereas no significant modification in the generation of CTL could be detected. It has been well established that the inoculation of rats and mice with large doses of MLM or other pathogenic mycobacteria induces deficits of in vitro immune functions, such as responses to polyclonal T-cell mitogens (32,38) and specific antigens (21) and an impairment of in vivo T cell-mediated immunity, such as delayed skin graft rejection (6,23), reduced delayed-type hypersensitivity response to sheep erythrocytes (6), and T-dependent antibody response to sheep erythrocytes (5,25,38).…”
Section: Discussionmentioning
confidence: 99%
“…Since IL2 production is ILl dependent (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), it could be hypothesized that the lack of ILl secretion by infected macrophages could play a role in the failure of IL2 production. Indeed, mouse strains susceptible to subcutaneous MLM inoculation display macrophage abnormalities, such as a diminished efficacity in controlling mycobacterial multiplication in vivo as compared with resistant mice (22) or an enhancement of superoxide dismutase activity in splenic macrophages of MLM receptive mice (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation